2019
DOI: 10.1016/j.jgr.2018.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Production of ginsenoside aglycone (protopanaxatriol) and male sterility of transgenic tobacco co-overexpressing three Panax ginseng genes: PgDDS, CYP716A47, and CYP716A53v2

Abstract: Background Protopanaxatriol (PPT) is an aglycone of ginsenosides, which has high medicinal values. Production of PPT from natural ginseng plants requires artificial deglycosylation procedures of ginsenosides via enzymatic or physicochemical treatments. Metabolic engineering could be an efficient technology for production of ginsenoside sapogenin. For PPT biosynthesis in Panax ginseng , damarenediol-II synthase (PgDDS) and two cytochrome P450 enzymes (CYP716A47 and CYP716… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…In 2011, Han [ 40 ] co-expressed PgDDS and PgCYP716A47 in yeast and found that protopanaxadiol-type sapogenins (PPDs) could be produced without the addition of dammarendiol and verified that CYP716A47 could catalyze the production of PPD from dammarendiol by in vitro enzymatic activity assays. In 2019, Gwak [ 41 ] co-transformed PgDDS , PgCYP716A47 and PgCYP716A53v2 ( PgCYP137 ) into tobacco and produced protopanaxatriol-type sapogenins (PPT) in transgenic tobacco, indicating that CYP716A53v2 can catalyze PPD to produce PPT. In 2014, Yan [ 42 ] heterologously expressed the UGTPg1 ( PgUGT1 ) gene in yeast and found that the UGTPg1-encoded protein could catalyze the production of rare ginsenoside CK from PPD as a substrate, as well as another novel compound, 20S-O-β-(D-glucosyl)-dammarenediol II (DMG).…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, Han [ 40 ] co-expressed PgDDS and PgCYP716A47 in yeast and found that protopanaxadiol-type sapogenins (PPDs) could be produced without the addition of dammarendiol and verified that CYP716A47 could catalyze the production of PPD from dammarendiol by in vitro enzymatic activity assays. In 2019, Gwak [ 41 ] co-transformed PgDDS , PgCYP716A47 and PgCYP716A53v2 ( PgCYP137 ) into tobacco and produced protopanaxatriol-type sapogenins (PPT) in transgenic tobacco, indicating that CYP716A53v2 can catalyze PPD to produce PPT. In 2014, Yan [ 42 ] heterologously expressed the UGTPg1 ( PgUGT1 ) gene in yeast and found that the UGTPg1-encoded protein could catalyze the production of rare ginsenoside CK from PPD as a substrate, as well as another novel compound, 20S-O-β-(D-glucosyl)-dammarenediol II (DMG).…”
Section: Discussionmentioning
confidence: 99%
“…An enzyme gene CYP6H (MZ27754) belonging to cytochrome P450 family was screened out from P. notoginseng. Bioinformatic analysis of CYP6H showed that CYP6H had high homology with CYP716A53V2, the nucleic acid similarity between the two genes is 94.88%, and the enzyme encoded by CYP716A53V2 could hydroxylated protopanaxadiol to protopanaxatriol (Gwak et al 2019). So, CYP6H might has the similar function as CYP716A53V2.…”
Section: Construction Of Transgenic Tobaccos For Protopanaxatriol Syn...mentioning
confidence: 99%
“…cell suspension culture Plant Cell Fermentation (PCF) Technology https://phytonbiotech.com/apis/paclitaxel/ Taxol Taxus spp. cell suspension culture Samyang’s plant cell culture technology https://www.samyangbiopharm.com/eng/ Triterpenoids Astragaloside A. membranaceus hairy root Elicitors ( Jiao et al., 2016 ) Diosgenin N. benthamiana Pooled screens and Overexpression ( Christ et al., 2019 ) Dammarenediol-II N. tabacum Overexpression ( Han et al., 2014a ) Ginsenoside P. ginseng www.nitto.com Protopanaxatriol/protopanaxadiol N. tabacum Overexpression ( Chun et al., 2015 ; Gwak et al., 2019 ) Squalene N. tabacum Compartmentalized metabolic engineering ( Pasoreck et al., 2016 ) Triterpene N. benthamiana Combinatorial transformation ( Reed et al., 2017 ) Triterpenoids C. asiatica hairy root Elicitors ( Baek et al., 2020 ) Tetraterpenoids β -Carotene Rice Overexpression ( Ye et al., 2000 ) β -Carotene Tomato Overexpression ( Apel and Bock, 2009 ) β -Carotene/carotenoids Maize Combinatorial transformation ( Zhu et al., 2008 ) Carotenoid Potato Overexpression ...…”
Section: Introductionmentioning
confidence: 99%